Assessing Cardiomyocyte DNA Damage Using Cardiovascular Magnetic Resonance T1 Mapping - Mizuki Ichikawa, MD; Shiro Nakamori, MD; Masaki Ishida, MD; Ryuji Okamoto, MD; Rie Ito, BSc, Agr; Junko Ishiura, MD; Masaki Ishiyama, MD; Taku Omori, MD; Keishi Moriwaki, MD; Emiyo Sugiura, MD; Naoki Fujimoto, MD; Tairo Kurita, MD; et al. (JACC: Advances)
Background: DNA damage in cardiomyocytes is a key pathological pathway in heart failure progression. It is a reversible process that precedes apoptosis and fibrosis. However, the utility of cardiovascular magnetic resonance T1 mapping for assessing DNA damage is uncertain. Objectives: This study aimed to evaluate the relationship between T1 mapping and cardiomyocyte DNA damage in patients with dilated cardiomyopathy (DCM). Methods: We identified 36 recent-onset DCM patients undergoing endomyocardial biopsy and serial 3T cardiovascular magnetic resonance before and after guideline-directed therapy. Extracellular volume (ECV) was quantified from native and postcontrast T1 mapping. DNA damage was assessed via poly(ADP-ribose) quantification in biopsy specimens, alongside collagen volume fraction (CVF) measurement. Results: Native T1 and ECV showed a strong correlation with histological CVF (r = 0.62 and r = 0.67, respectively; P < 0.001), while native T1 moderately correlated with the severity of cardiomyocyte DNA damage (r = 0.41, P = 0.01), but ECV did not. This association remained significant after controlling for CVF. Patients with substantial DNA damage have significantly higher native T1 for an equivalent ECV (P = 0.004). In the absence of severe fibrosis, myocardial tissue recovery following guideline-directed therapy, along with improvements in left ventricular ejection fraction and reductions in left ventricular cavities, was associated with baseline DNA damage (r = −0.49, P = 0.004) but not with CVF (r = −0.17, P = 0.38). Conclusions: Native T1 mapping effectively detects DNA damage and fibrosis, revealing different pathophysiological mechanisms behind the increased native T1 and ECV. A disproportionate increase in native T1 relative to ECV suggests early myocardial injury preceding fibrosis in DCM, with potential implications for myocardial tissue recovery after guideline-directed therapy.